The Flp type IV pilus operon of Mycobacterium tuberculosis is expressed upon interaction with macrophages and alveolar epithelial cells - Alteri, Christopher J.; Rios-Sarabia, Nora; De la Cruz, Miguel A.; González-y-Merchand, Jorge A.; Soria-Bustos, Jorge; Maldonado-Bernal, Carmen; Cedillo, María L.; Yáñez-Santos, Jorge A.; Martínez-Laguna, Ygnacio; Torres, Javier; Friedman, Richard L.; Girón, Jorge A.; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
The genome of Mycobacterium tuberculosis (Mtb) harbors the genetic machinery for assembly of Fimbrial low-molecular-weight protein (Flp) type IV pilus. Presumably, the Flp pilus is important for pathogenesis, however, it remains unclear whether the pili genes are transcribed in culture or during infection of host cells. The aim of this study was to shed light on the expression of the Flp pili-assembly genes (tadZ, tadA, tadB, tadC, flp, tadE, and tadF) in Mtb growing under different growth conditions (exponential phase, stationary phase, and dormancy NRP1 and NRP2 phases induced by hypoxia), during biofilm formation, and in contact with macrophages and alveolar epithelial cells. We found that expression of tad/flp genes was significantly higher in stationary phase than in exponential or NRP1 or NRP2 phases suggesting that the bacteria do not require pili during dormancy. High levels of gene expression were recorded when the bacilli were in contact for 4 h with macrophages or epithelial cells, in comparison to mycobacteria propagated alone in cultured medium. An antibody raised against a 12-mer peptide derived from the Flp pilin subunit detected the presence of Flp pili on intracellular bacteria infecting eukaryotic cells. All together, these are compelling data showing that the Flp pili genes are expressed during interaction of Mtb with host cells and highlight a role for Flp pili in colonization and invasion of the host subsequently promoting bacterial survival during dormancy.